Prevention Practices and Legal Rules for Handling Pandemics in The Prophetic Sirah - Hafidi, Hakima; Mauhub, Fauzi (Islamic Religious Education Departement, 2021)
This study focuses on highlighting the devotional and social preventive applications related to the epidemics, by shedding the lights on some stations from the biography and the sunnah of the Prophet peace be upon him, this will contribute to the prevention of epidemics, especially Coronavirus, by following the teaching of Sharia and the approach of the Prophet, peace be upon him, in dealing with such types of epidemics that appeared in his era. To achieve the goal of this study, we followed two approaches: inductive and analytical. We start by presenting the Hadiths that dealt with the topic of prevention in the Sunnah and biography, then we analyze the most prominent methods and applications followed by the Prophet in the prevention of epidemics. The research reached the following results, most of them, the precedence of Sunnah through what was illustrated in the Prophet’s biography in demonstrating the means of devotional and medical prevention against epidemics and their effectiveness in people’s lives. Finally, worshipping by obeying orders and avoiding prohibitions is a reason to prevent the epidemic.